KEBIJAKAN FORMULASI PENGATURAN PIDANA PENJARA TERBATAS DALAM PERUNDANG-UNDANGAN INDONESIA PERSPEKTIF IUS CONSTITUENDUM - Putu Sekarwangi Saraswati (Faculty of Law, Mahasaraswati University, Denpasar, 2020)
One of the efforts to tackle crime is to use criminal law with criminal sanctions. The type of criminal sanction that is most often used to tackle crime problems is imprisonment. Meanwhile, in its development, imprisonment is a type of criminal sanction that is currently receiving sharp scrutiny from experts. Many sharp criticisms have been directed at this type of criminal deprivation of independence, both in terms of its effectiveness and in terms of the other negative consequences that accompany it. In the new Penal Code Concept Book I in 1982 proposed a type of